Association of shift work with cardiovascular disease risk among Chinese workers. (3rd August 2021) - Feng, Xiaobing; Qiu, Weihong; Cheng, Man; Liang, Ruyi; Xu, Tao; Zhou, Min; He, Meian; Zhang, Xiaomin; Yuan, Jing; Wang, Dongming; Chen, Weihong
ABSTRACT: To evaluate the association of shift work with 10-year cardiovascular disease (CVD) risk among Chinese workers. We included 23, 064 workers in the first follow-up of the Dongfeng-Tongji cohort study. Questionnaires and physical examinations were conducted to collect data for all participants. Framingham Risk Score was calculated according to the multivariable risk algorithms, and used to evaluate 10-year CVD risk. Logistic regression models were used to assess the relationship between shift work and 10-year CVD risk. Among 23, 064 individuals, 51.92% of workers suffered shift work, and the proportions of shift work duration of 1-<10, 10-<20, and ≥20 years were 17.29%, 17.35% and 17.30%, respectively. Compared with individuals without a shift work history, the odds ratios (ORs) and 95% confidence intervals (CIs) of 10-year CVD were 1.027 (0.900–1.173), 1.058 (0.927–1.206) and 1.191 (1.036–1.368) for individuals with shift work duration of 1-<10 years, 10-<20 years, and ≥20 years, respectively, after adjusting for potential confounders. And the association was more obvious in males. When shift work and obesity were combined, the OR (95%CI) of high 10-year CVD risk (3.373, 2.390–4.761) was significantly increased for obese individuals with shift work of ≥20 years. Besides, the OR (95%CI) for higher 10-year CVD risk associated with shift work decreased as the leaving shift work duration prolonged. Shift work is associated with a higher 10-year CVD risk, especially among males. Obesity has a synergistic effect on such association while leaving shift work reduces such association.